Effect of acute L-carnitine supplementation on blood lactate, glucose, aerobic and anaerobic performance in elite male artistic gymnasts - Arazi, H.; Mehrtash, M. (Baltic Journal of Sport and Health Sciences, 2017)
Background. Probably L-Carnitine can induce the increase of Pyruvate dehydrogenase activity, decrease of lactic acid production and performance improvements due to the reinforcement of long chain fatty acid oxidation and stabilize of coASH to free COA. Based on this, the aim of our study was to investigate the effects of acute L-Carnitine supplementation on blood lactate, glucose, VO2max and anaerobic power in elite male artistic gymnasts. Methods. Eighteen male artistic gymnasts were randomly assigned to supplementation (n = 9) or placebo (n = 9) groups. In a double blind design, subjects participated in two tests with a break of one week between them. Subjects ingested 3 grams of L-Carnitine or placebo (maltodextrin) 90 minutes before aerobic and anaerobic exercise protocols. We used a 20 m shuttle run as an aerobic exercise protocol and running based anaerobic sprint test (RAST) as an anaerobic exercise protocol. Blood samples were collected 5 minutes pre and 4 minutes post-tests for the analysis of lactate and glucose. Results. L-Carnitine group had significantly lower lactate concentration than placebo group after tests (p < .05). L-Carnitine group had significantly higher blood glucose (p < .05) compared with placebo group, too. Also VO2max as well as mean and maximum power in L-Carnitine group were significantly higher than those in placebo group (p < .05). Conclusions. These findings indicated that acute oral supplementation of L-Carnitine can probably induce fatigue decrease and improvement of aerobic and anaerobic performance in elite male artistic gymnasts. (Abstract)